Section Commentary. Cultural, Social, and Linguistic Aspects of School Consultation - Shriberg, David; Little, Tiondra J.; McPherson, Casey (Handbook of Research in School Consultation: Empirical Foundations for Educational and Human Sciences: Third Edition, 2026)
This chapter provides commentary on the four chapters in the section on the cultural, social, and linguistic aspects of school consultation. In each case, the authors pose penetrating insights and highlight a need for more extensive literature utilizing the full spectrum of research methodologies. In this spirit, this chapter suggests that strong consultation in these topical domains might be guided by the questions: (a) What is our mindset as researchers?, (b) Is the researcher culturally humble?, and (c) What might be most helpful? Building off the “what might be helpful” question, the commentary closes by framing two relevant areas where consultation research is lacking-consultation research in support of multiracial students and consultation research to address antisemitism and support Jewish students-as ways to expand the cultural, social, and linguistic aspects of school consultation literature. © 2026 selection and editorial matter, S. Andrew Garbacz, Daniel S. Newman, William P. Erchul, and Susan M. Sheridan; individual chapters, the contributors.
Keywords: dept.csp

The Neurospicy Queer Experience: Insights Into the Lived Experiences & Counseling Needs of Transgender and Gender Expansive Adults with ADHD - Gorski, J.; Bonjo, L.; Sassu, Kari; Councilor, KC (Journal of LGBTQ Issues in Counseling, 2026)
Keywords: ADHD; Expansive; Human sexuality; Lived experience; Qualitative research; Queer; Transgender; dept.com; dept.csp; gender affirming care; gender expansive; neurodivergence; neuroqueer; neurospicy